Ambedkar and the Struggle for Women's Equality. Issue 1 (June 2016) - Vajpeyi, Ananya
The article highlights Dr B. R. Ambedkar's battle for equality and sketches out his political campaigns which were designed to boycott caste rules and allow 'untouchables' access to temples, wells and other civic resources—all with the intention to raise public consciousness against the practice of untouchability. And, importantly, the article talks about how women were included in these campaigns. It throws light on how Ambedkar addressed women as mothers and social change initiators; and how, as a lawyer and legislator, he engaged with the issues of not only the 'untouchable' women but also of women as a part of the labour force.